Non-timber forest product databases - Lay Cheng Tan; Ruíz Pérez, M.; Ibach, M. (1996)
A number of databases on non-timber forest products (NTFP) have been produced but any information available is mostly scattered and poorly advertised. It is necessary to survey the existence of such databases to provide information to interested and potential actors on what is available on NTFP, to co-ordinate future work and to avoid duplication. The Center for International Forestry Research conducted a survey on NTFP databases principally to gather information and to assess such databases and their users. A workshop was held in December 1995 and this Working Paper incorporates results of the survey, brief reports of some of the databases and conclusions from the workshop.